Saturn: An Auto-Ethnographic Enquiry into Contemporary Astrological Practice - Hathway, Liz (Journal for the study of religion, nature and culture, 2019)
Using qualitative and reﬂexive research methodology I explore the cultural role that the planet Saturn plays in contemporary communities of astrologers and the astrological way of life. Through an exploration of Saturn as a mythical ﬁgure and as symbol, I ﬁrst discuss astrology’s cultural background and demonstrate that astrologers have a cultural memory that has remained largely loyal to its roots in the Mesopotamian and Hellenistic periods. I then illuminate the way in which for contemporary astrologers sun-sign astrology functions as a contemporary expression of ancient myth. In addition, I examine the importance of the Saturn Return, which has since become an important symbol of transition, a rite of passage, and a modern form of enchantment that not only marks a life transition but also has the potential to effect one.